2021
DOI: 10.1016/j.psj.2021.101056
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proteolytic enzyme activities, tenderness-related traits, and quality properties of spent hen meat affected by adenosine 5′-monophosphate during cold storage

Abstract: A mechanism of postmortem tenderization by adenosine 5′-monophosphate ( AMP ) on spent hen meat was investigated. Breast meat samples were made into a rectangular size of 7.5 × 5 × 2 cm and grouped into 5 different treatments, followed by immersion for 24 h at 4 ± 2°C in AMP marinade solutions of 0, 15, 30, 45, and 60 mmol/L that dissolved in 0.9% (w/v) saline solution. To investigate the enzymatic changes and tenderness-related traits, samples were stored until day 5 at a temperature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 66 publications
1
22
1
Order By: Relevance
“…This condition will eventually generate a lower percentage of water retained within the muscle, thus initiating higher cooking loss during processing ( Dang et al., 2018 ). The lower cooking loss is also strongly correlated with the lower juiciness perception of meat products ( Barido and Lee, 2021 ; Jeong et al, 2020 ). The cooking loss and WHC found in this study were within the range reported in a previous study on commercial broilers ( Jeong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 95%
“…This condition will eventually generate a lower percentage of water retained within the muscle, thus initiating higher cooking loss during processing ( Dang et al., 2018 ). The lower cooking loss is also strongly correlated with the lower juiciness perception of meat products ( Barido and Lee, 2021 ; Jeong et al, 2020 ). The cooking loss and WHC found in this study were within the range reported in a previous study on commercial broilers ( Jeong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 95%
“…Low pH values are unfavorable for the meat industry. It is a sign of excessive protein denaturation ( Huff-Lonergan and Lonergan, 2005 ), and is associated with meats with low water retention capacity, tougher textures, and lower cooking yields after cooking ( Barido et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The upregulation of endogenous proteolytic enzymes due to their high serine and metalloprotease activity during post-mortem tenderization was also discovered after marination of the chicken breast with CM mushroom extract [17]. The moderate proteolytic activity of the CM mushroom at 4.57 unit/mL and abundant 5′-adenosine monophosphate concentration was thought to be responsible for the above-mentioned effects [18].…”
Section: Introductionmentioning
confidence: 99%